Law School as Social Innovation - Sossin, Lorne (Victoria University of Wellington Law Review, 2017)
Legal education is in the midst of a range of challenges and disruptions. This address outlines these dynamics, and explores the potential of social innovation as a model for law schools which both responds to current challenges and enhances resilience in the face of disruption. By reframing legal education as facing outward, and advancing its public interest mandate through partnerships, collaboration and academic initiatives designed to solve social problems, law schools can enhance the student learning experience, generate new forms of legal knowledge and thrive at a time of rapid change. Address delivered at the Australian Law Teachers Association (ALTA) 2016 Conference in Wellington on 8 July 2016.